AUGMENTED REALITY TECHNOLOGY IN EDUCATION: A LITERARY STUDY ON SCIENCE LEARNING - Kasmudin Mustapa; Nanda Aprilia Lampasio; Zaenab (Indonesian Journal of Education (INJOE), 2023)
In the study of literature on the use of Augmented Reality (AR) technology in science learning, some important conclusions were found. The use of AR in science learning can improve student understanding of concepts, student involvement, critical thinking skills, and student information retention. The visual and sensory experiences provided by AR help students visualize complex concept, increase their motivation in learning, and strengthen their understanding of science concepts studied. However, it is important to continue doing further research to understand the impact of AR on student learning performance and how to effectively integrate this technology into student learning experiences. These conclusions may vary depending on the context and characteristics of different students, so the use of AR should be tailored to students' needs and follow the best guidelines